Assessing the Correlation Between Langerhans Cells Population and Prognosis of Tongue Squamous Cell Carcinoma - Narges Ghazi; Nasrollah Saghravanian; Pooya Saeedi; Mohammad Mahdi Maboudinezhad (Clinical and Experimental Dental Research)
ABSTRACT Background and Objective Tongue squamous cell carcinoma (TSCC) is the most prevalent oral cancer. Despite considerable advancements in treatment, the 5‐year survival rate remains relatively unchanged. Langerhans cells (LCs) play an important role in antitumor immunity. Therefore, we attempt to evaluate the correlation between the LC count and disease prognosis. Materials and Methods Histopathologic slides from 24 cases, with at least 2 years of follow‐up, were selected and categorized into early‐stage (12 cases) and advanced‐stage (12 cases) groups. An additional 12 slides of normal tissue comprised the control group. Immunohistochemical staining with the CD1a marker was performed to analyze the density of LCs. Statistical analysis assessed the impact of CD1a immune expression on patient survival and other variables such as age, gender, stage, and histopathological grade. Results Comparison of CD1a+ cell counts across the three groups revealed a significant decrease in the advanced group. Furthermore, a lower count of CD1a+ cells correlated with poorer disease‐free survival (DFS) (p < 0.001) and overall survival (OS) (p = 0.049). Although the CD1a+ cell count did not independently affect OS significantly (p = 0.210), it did show a significant impact on DFS as an independent variable (p = 0.002). Conclusion The significant correlation between CD1a expression and patients' prognosis and survival rates suggests that CD1a+ cells could serve as a crucial prognostic factor in the management and treatment of TSCC.